1994
DOI: 10.21000/jasmr94010099
|View full text |Cite
|
Sign up to set email alerts
|

Manganese and Iron Removal from Coal Mine Drainage by Use of a Green Algae-Microbial Mat Consortium

Abstract: At the Tennessee Valley Authority's Fabius Coal Mine, Alabama, manganese was more effectively removed from a pond containing an algae mat consortium and limestone substrate than from ponds containing only limestone or pea gravel substrates. The algae mat resulted from the integration of a microbial mat and volunteer filamentous green algae. The microbial mat consisted of blue-green algae (predominately Oscillatoria spp.) and bacteria isolated from the site, cultured in the laboratmy, and returned to the site. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Phillips et al (1994) conducted similar experiments in AMD from coalmines and obtained similar results. For a developing country like India, passive treatment systems, which have no energy requirements, are preferred.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Phillips et al (1994) conducted similar experiments in AMD from coalmines and obtained similar results. For a developing country like India, passive treatment systems, which have no energy requirements, are preferred.…”
Section: Discussionmentioning
confidence: 60%
“…Mats have been reported to reduce Pb, Cd, Cu, Zn, Co, Cr, Fe, and Mn. Mats are nitrogen fixing and photosynthetic (Phillips et al 1994), and so are selfsufficient solar-driven ecosystems with few growth requirements. Mats have been found to reduce selenate to elemental selenium (Bender et al 1991) Degradation of recalcitrant organic contaminants has also been observed under both dark and light conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplanktons have also been reported to be quite efficient in heavy metal removal from AMD (Bender et al 1989(Bender et al , 1991Phillips et al 1994;Sheoran and Bhandari 2005). Kalin et al (2004) reported that algae like Chara nitella provide a simple, long term means to remove uranium and other radionuclides from uranium mining effluents.…”
Section: Introductionmentioning
confidence: 99%
“…Active systems involve technologies such as pH modification, ion exchange, biology-based treatments, adsorption, electrochemical treatment and physical process technologies. Passive treatment includes chemical passive treatment by the addition of chemicals such as limestone, polymers or others (Braun et al, 2001;Brodie et al, 1993;Ziemkiewicz et al, 1997) and biological passive treatment represented by primary constructed wetlands and secondary algal systems or special bioreactors (Braun et al, 2001;Foster, 1982;Phillips et al, 1994;Davison, 1993;Duc et al, 1998). The passive treatment systems, and in particular constructed wetlands, are advantageous mainly because they cause comparably low costs, are truly self-sustaining and are suitable for the treatment of mine water from abandoned mines (Braun et al, 2001).…”
Section: Glucosinolates and Biofumigationmentioning
confidence: 99%